Changes in Alpine Soil Bacterial Communities With Altitude and Slopes at Mount Shergyla, Tibetan Plateau: Diversity, Structure, and Influencing Factors - Zou, Zehao; Yuan, Ke; Ming, Lili; Li, Zhaohong; Yang, Ying; Yang, Ruiqiang; Cheng, Weibin; Liu, Hongtao; Jiang, Jie; Luan, Tiangang; Chen, Baowei (Frontiers in Microbiology, 2022)
Alpine ecosystem as one of the most representative terrestrial ecosystems has been highly concerned due to its susceptibility to anthropogenic impacts and climate changes. However, the distribution pattern of alpine soil bacterial communities and related deterministic factors still remain to be explored. In this study, soils were collected at different altitudes and slope aspects of the Mount (Mt.) Shergyla, Tibetan Plateau, and analyzed using 16S rRNA gene-based bioinformatics approaches. Acidobacteriota and Proteobacteria were consistently identified as the two predominant phyla in all soil samples, accounting for approximately 74% of bacterial community. The alpha diversity of soil bacterial community generally increased as the vegetation changed with the elevated altitude, but no significant differences in alpha diversity were observed between the two slopes. Beta diversity analysis of bacterial community showed that soil samples from the north slope were always differentiated obviously from the paired samples at the south slope with the same altitude. The whole network constituted by soil bacterial genera at the Mt. Shergyla was parsed into 8 modules, and Elev-16S-573, Sericytochromatia, KD4-96, TK10, Pedomicrobium, and IMCC26256 genera were identified as the ‘hubs’ in the largest module. The distance-based redundancy analysis (db-RDA) demonstrated that variations in soil bacterial community thereof with the altitude and slope aspects at the Mt. Shergyla were closely associated with environmental variables such as soil pH, soil water content, metal concentrations, etc. Our results suggest that environmental variables could serve as the deterministic factors for shaping the spatial pattern of soil bacterial community in the alpine ecosystems.